Delayed diagnosis of tuberculosis in persons living with HIV in Eastern Europe: associated factors and effect on mortality - a multicentre prospective cohort study - Kraef, Christian; Bentzon, Adrian; Panteleev, Alexander; Skrahina, Alena; Bolokadze, Natalie; Tetradov, Simona; Podlasin, Regina; Karpov, Igor; Borodulina, Elena; Denisova, Elena; Azina, Inga; Lundgren, Jens; et al. (BMC infectious diseases, 2021)
Early diagnosis of tuberculosis (TB) is important to reduce transmission, morbidity and mortality in people living with HIV (PLWH).